Visualising the scales of ethnic diversity in London using a multilevel entropy index. (October 2020) - Harris, Richard
A challenge emerging from the literature on measuring and modelling segregation at multiple scales is how to map the results. This Featured Graphic uses a method based on the CMY colour model, allowing each of the C, M and Y values to represent one of the micro-, meso- and macro-levels of analysis separately, then combining them in an overall map. It presents the method using a new index, a multilevel index of diversity, with a case study looking at the ethnic diversity of state-school pupils living in London's neighbourhoods.